«You will be this way because that is how we are raising you»: youth, indoctrination and fascistization during the Chilean dictatorship, 1973-1983. - González, Yanko (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article addresses the purposes of formative and loyalty inspiring actions carried out by the organisations of the civic-military Chilean dictatorship: Frente Juvenil de Unidad Nacional (Youth Front of National Unity) and Secretaría Nacional de la Juventud (National Secretariat of Youth). By examining the political and organizational references of said entities and through diverse documental sources and life narrations, it is sought to reconstruct the main instances of indoctrination of young people considering the ideological principles and the palingenetic myths of the regime. In addition to the above, and making special emphasis on the effects of said educational instances on the production and experimentation of young subjects, this work analyses the implications of the documental evidence as well as the memories and biographical narratives, in order to understand this objective inscribed in, what we sustain, was a real process of fascistisation that took place in the first years of the Chilean dictatorship.